The ship of the desert. The dromedary camel (Camelus dromedarius), a domesticated animal species well adapted to extreme conditions of aridness and heat - Bornstein, S. (Rangifer, 1990)
The dromedary camel (Camel dromedarius) is extremely well adapted to life in hot and arid lands. In terms of physiological adaptation to heat and water deprivation it surpasses by far every other large animal of which data have been collected. None of the adaptive mechanisms to cope with the environmental stresses are unique to the Arabian camel, but the efficiency of its adaptation is superior. At high ambient temperatures the camels adapt to the scarcity of water by reducing their faecal, urinary and evaporative water losses. During dehydration, the kidneys reduce water losses both by decreasing the glomerual filtration rate and by increasing the tubular reabsorption of water. Also their ability of regulating their body temperature from 34.5-40.7 °C conserves a lot of water, when most needed.
Keywords: dromedary camel; heat-adaptation; water conservation